A review of Malaysian experience in tissue engineering research and development:A bibliometric study using online databases - Ahmad Radzi, Muhammad Aa’zamuddin; Zainuddin, Zainul Ibrahim; Abdulahi Hashi, Abdurezak; Mohamad, Mohd Yusof; Md Nazir, Noorhidayah; Hashim, Rosyafirah; Mat Nawi, Nur Farhana; Sha'ban, Munirah (International Islamic University Malaysia, 2016)
Tissue engineering research serves to overcome the major obstacles in organ transplantation.The obstacles include insufficient supply of organs, immunoreaction, subsequent rejection between donor organs and recipient’s body as well as life-long immunosuppression dependence. This paper intends to summarize the progress of tissue engineering in Malaysia. The online databases of Elsevier’s SCOPUS and Thomson Reuter’s Web of Science™ Core Collection were accessed. The publicationsrelated to TE from 1985 till 2015 were scrutinized. The results show an increasing trend in tissue engineering research and development in Malaysia. It can be appreciated that after 30 years of its inception, tissue engineering expands at the rate of R2 = 0.3718. The search’s result came out with only 311 publications when compared to the overall progress of tissue engineering worldwide. It is hoped that the outcomes of this study could serve as a point of reference for researchers on the status of tissue engineering research and development in Malaysia. It is hoped that the findings of this study could assist Tissue Engineering researchers in Malaysia to identify the strengths, weaknesses, opportunities and obstacles towards further enhancement in their activities. Consolidating, realigning and re-strategizing those initiatives should also be seen within the context of nurturing potential and budding researchers.